Edukasi Tentang Faktor Resiko Penyakit Miopi Pada Mahasiswa Manajemen Informasi Kesehatan Tingkat III Stikes Santa Elisabeth Medan - Pomarida Simbolon; Angelia Pasaribu; Wetty Mayanora Mendrofa (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Myopia is a condition where distant objects cannot be displayed clearly on the retina. The aim of the research is to determine the incidence of myopia in school-aged children in Trenggalek district. Myopia is the cause of decreased vision in school-aged children, good vision is needed in the teaching and learning process. The aim of this research is to provide education about hypertension to respondents (MIK students). The research design uses pre-experimental design, using one group pretest and post-test design. The sample was 14 respondents. Chi-Square Statistical Test Results What was obtained was that 68.46% of students did not understand what myopia was and after counseling, 86.92% understood what myopia was.